Signal Adaptive System for Space/Spatial-Frequency Analysis. (11th January 2010) - Ivanović Ivanović, Veselin N. Veselin N.; Jovanovski Jovanovski, Srdjan Srdjan
Abstract : This paper outlines the development of a multiple-clock-cycle implementation (MCI) of a signal adaptive two-dimensional (2D) system for space/spatial-frequency (S/SF) signal analysis. The design is based on a method for improved S/SF representation of the analyzed 2D signals, also proposed here. The proposed MCI design optimizes critical design performances related to hardware complexity, making it a suitable system for real time implementation on an integrated chip. Additionally, the design allows the implemented system to take a variable number of clock cycles (CLKs) (the only necessary ones regarding desirable—2D Wigner distribution-presentation of autoterms) in different frequency-frequency points during the execution. This ability represents a major advantage of the proposed design which helps to optimize the time required for execution and produce an improved, cross-terms-free S/SF signal representation. The design has been verified by a field-programmable gate array (FPGA) circuit design, capable of performing S/SF analysis of 2D signals in real time.